Traumatic Fracture of the Medial Coronoid Process in Two Dogs - Yovich, J. C.; Read, R. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Acute traumatic fracture of the me-dial coronoid process occurred in two adult dogs. The fracture was the sole injury in one dog, but was associated with further elbow trauma in the other. Surgical removal of the fractured portion of medial coronoid process resulted in a rapid return to normal elbow function which was sustained on long-term follow-up. Radiographs showed some osteophyte formation within the elbow joints at one year postoperatively. Two years later, repeat radiography of the elbow of one of the dogs did not show any further osteophyte production. In contrast, the surgical removal of fragmented coronoid processes frequently results in continuing lameness, reduced range of elbow movement and progressive osteoarthritis.Removal of a traumatically fractured portion of the medial coronoid process in two adult dogs resulted in a rapid return to soundness. Elbow function in both dogs remained normal on long-term follow-up.
Keywords: Traumatic fracture; medial coronoid process